Museu Histórico Fernando Ferrari: estratégia de fortalecimento da identidade local 2018-2019 - Bayer, Luiza Gutheil (2020)
The presente work had as objetive comprehend in what way the Historical Musem Fernando Ferrari in São Pedro do Sul city, Rio Grande do Sul, can be a vector for the diffusion of municipal history activating the memory of local residents. Also, demonstrate how a museum can fulfill the social function of strengthening the self- esteem and local identity of São pedrenses. Took place during the construction of this work, the identification, the registry and the organization of the documentary and photograpy collection in that musem, in order to make it more agile and effective the research performed in the place, enabling thus to rescue and reassembling the São Pedro do Sul history; as the reorganization of the objects of the collection, in order to understand the extend of this, facilitate the resarch and value the pieces on display. To understand how it happens the relationship of the Historical Museum Fernando Ferrari with the audience, it was made a bibliographic review related to museum, cultural heritage,heritage education, cultural identity, São Pedro do Sul and Historical Musem Fernando Ferrrari themes, deepning in the accomplished actions by this musem between 2018 and 2019. From this analysis, I a booklet was created to contribute with the visitation and actions accomplished by the musem.